Carbon-coated vanadium-manganese-sodium phosphate positive electrode material, sodium ion battery, and preparation method and application of carbon-coated vanadium-manganese-sodium phosphate positive electrode material and sodium ion battery

By adopting carbon coating technology and sol-gel-high-temperature sintering method in the vanadium manganese sodium phosphate positive electrode material, the problems of poor conductivity and insufficient cycle stability of the existing sodium ion battery positive electrode materials are solved, and high-performance and low-cost positive electrode materials are achieved, which promotes the commercial application of sodium ion batteries.

CN119637830APending Publication Date: 2025-03-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311195846.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have problems such as poor electronic conductivity and poor cycle stability, and the raw materials such as vanadium used in the synthesis process are highly toxic and costly, which limits their practical application.

Method used

By using carbon coating technology in the sodium manganese vanadium phosphate positive electrode material, the conductivity is improved and the ginger-Taylor effect of manganese element is suppressed, and the preparation is carried out by sol-gel-high-temperature sintering method, which simplifies the process and reduces the cost.

Benefits of technology

It achieves high electronic conductivity and excellent electrochemical performance, reduces material production costs, improves the cycle stability and rate performance of the positive electrode material, and promotes its commercial development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637830A_ABST
    Figure CN119637830A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-coated vanadium manganese sodium phosphate positive electrode material, a sodium ion battery and a preparation method and application thereof, and belongs to the technical field of sodium ion batteries. The preparation method provided by the invention comprises the following steps: (1) heating a mixture containing a sodium source, a vanadium source, a manganese source, a phosphorus source, a carbon source and water I, stirring until gel is formed, and drying to obtain a precursor; and (2) carrying out ball milling on the precursor, and then placing the precursor in an inert gas atmosphere for heating II to obtain the carbon-coated vanadium manganese sodium phosphate positive electrode material. The preparation method provided by the invention is simple, the raw material composition is simple, quantitative production is easy, and the prepared carbon-coated vanadium manganese sodium phosphate has good crystallinity, high working potential and excellent cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of sodium ion batteries, and in particular relates to a carbon-coated sodium manganese vanadium phosphate positive electrode material, a sodium ion battery, and a preparation method and application thereof. Background Art

[0002] The higher reserves and more even distribution of sodium in the earth's crust, as well as the similar charge-discharge mechanism of sodium-ion batteries as lithium-ion batteries, create conditions for the manufacture of low-cost sodium-ion batteries. Promoting the development of sodium-ion batteries and achieving a complementary pattern with lithium-ion batteries is of great significance to the development of clean energy. However, the large radius and large mass of sodium ions limit the further development of sodium-ion batteries. In order to increase the energy density of batteries, obtaining suitable positive electrode materials is the key to improving specific capacity.

[0003] At present, the existing cathode materials mainly include polyanionic compounds, layered transition metal oxides, Prussian blue analogs and organic compounds. Among them, NASICON structure cathode materials have excellent structural stability and high ionic conductivity due to their unique crystal framework structure. As a representative of NASICON structure cathode materials, Na3V2(PO4)3(NVP) can provide about 110mAh·g -1 The reversible capacity and energy density are about 370Wh·kg -1 However, the poor rate performance of sodium vanadium phosphate is caused by its poor electronic conductivity. In addition, the use of toxic and expensive vanadium in the synthesis process is not conducive to its practical application, so it is still far from the goal of practical application.

[0004] Due to the flexible tunability of the NASICON structure, different choices of transition metal sites were verified by replacing V with various inexpensive transition metal elements in NVP. 3+ / Mn 2+ The redox center brings a series of positive electrode materials, improves the output voltage and specific capacity, and manganese is cheap and has low toxicity. However, Mn-based compounds have a serious Jahn-Taylor effect, resulting in poor cycle stability. Therefore, it is urgent to find a low-cost and simple preparation method of high-performance sodium vanadium manganese phosphate positive electrode material and apply it to sodium ion batteries. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a carbon-coated sodium vanadium manganese phosphate positive electrode material, a sodium ion battery, and a preparation method and application thereof. The carbon-coated sodium vanadium manganese phosphate positive electrode material can be prepared on a large scale through a simple preparation method. The conductivity can be improved by in-situ coating of carbon while suppressing the Jahn-Taylor effect of the manganese element, which can enhance the electrochemical properties of the positive electrode material and reduce the material production cost, thereby obtaining a high-performance sodium vanadium manganese phosphate positive electrode material and promoting its commercial development.

[0006] In order to achieve the above-mentioned invention object, this application provides the following technical solutions:

[0007] On the one hand, the present application provides a method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material, comprising the following steps:

[0008] (1) heating a mixture containing a sodium source, a vanadium source, a manganese source, a phosphorus source, a carbon source, and water for 1 h, stirring until a gel is formed, and drying to obtain a precursor;

[0009] (2) ball milling the precursor, and then heating it in an inert gas atmosphere II to obtain the carbon-coated sodium manganese vanadium phosphate positive electrode material.

[0010] Optionally, the atomic substance ratio of sodium, vanadium, manganese and phosphorus in the sodium source, vanadium source, manganese source and phosphorus source in step (1) is 3-4:1-2:0-1:3.

[0011] Preferably, the ratio of the amount of atomic substances of sodium, vanadium, manganese and phosphorus in the sodium source, vanadium source, manganese source and phosphorus source in step (1) is 3-4:1.6-1.8:0.2-0.4:3.

[0012] Optionally, the heating I in step (1) includes heating I-1 and heating I-2;

[0013] The temperature of the heating I-1 is 60 to 100° C.;

[0014] The heating time of I-1 is 1 to 3 hours;

[0015] The temperature of the heating I-2 is 100-200°C.

[0016] Optionally, the temperature of the heating I-1 is independently selected from any value of 60°C, 70°C, 80°C, 90°C, 100°C, or any range therebetween.

[0017] Optionally, the heating time of I-1 is independently selected from any value among 1h, 1.5h, 2h, 2.5h, 3h, or any range between two of them.

[0018] Optionally, the sodium source in step (1) includes sodium citrate and / or sodium carbonate.

[0019] Optionally, the vanadium source in step (1) includes one or more of ammonium metavanadate, sodium vanadate, vanadium pentoxide, hydrated vanadium oxalate and vanadium chloride.

[0020] Optionally, the manganese source in step (1) includes one or more of manganese acetate, manganese carbonate, manganese sulfate, manganese chloride and manganese carbonate.

[0021] Optionally, the phosphorus source in step (1) includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphoric acid.

[0022] Optionally, the carbon source in step (1) includes one or more of sodium citrate, citric acid, glucose and hexadecyltrimethylammonium bromide.

[0023] Optionally, the stirring speed in step (1) is 300 to 1000 rpm.

[0024] Optionally, the drying temperature in step (1) is 100-200°C.

[0025] Optionally, the drying temperature in step (1) is independently selected from any value of 100°C, 120°C, 140°C, 160°C, 180°C, 200°C or any range between two values.

[0026] Optionally, the heating II in step (2) is segmented heating;

[0027] The staged heating is firstly heating to 300-400° C., keeping the temperature for 3-5 hours, and then heating to 700-900° C., keeping the temperature for 6-10 hours.

[0028] Optionally, the rotation speed of the ball mill in step (2) is 300-400 rpm.

[0029] Optionally, the inert gas in step (2) includes argon or nitrogen.

[0030] In a second aspect, the present application provides a carbon-coated sodium manganese vanadium phosphate positive electrode material prepared by the above preparation method.

[0031] In a third aspect, the present application provides an application of the above-mentioned carbon-coated sodium manganese vanadium phosphate positive electrode material in the preparation of a sodium ion battery.

[0032] In a fourth aspect, the present application provides a sodium ion battery, which comprises the above-mentioned carbon-coated sodium vanadium manganese phosphate positive electrode material.

[0033] Compared with the prior art, this application has the following beneficial effects:

[0034] (1) The present application improves the electronic conductivity and electrochemical properties of sodium vanadium manganese phosphate by adjusting the ratio and type of sodium source, vanadium source, manganese source and phosphorus source, thereby obtaining a carbon-coated sodium vanadium manganese phosphate positive electrode material with high electronic conductivity and excellent electrochemical properties.

[0035] (2) This application uses a sol-gel-high temperature sintering method to replace V with Mn in the sodium vanadium phosphate electrode material, and improves the conductivity by in-situ carbon coating while suppressing the Jan-Taylor effect of the manganese element, which can improve the electrochemical performance of the positive electrode material and reduce the material production cost. At the same time, the preparation method provided by this application is simple, the raw material composition is simple, and it is easy to quantify the production. The prepared carbon-coated sodium vanadium manganese phosphate has good crystallinity, high working potential, excellent cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a scanning electron microscope image of the carbon-coated sodium manganese vanadium phosphate prepared in Example 1 of the present application;

[0037] Figure 2 This is the XRD pattern of the carbon-coated sodium manganese vanadium phosphate prepared in Example 1 of the present application;

[0038] Figure 3 This is a rate performance diagram of the carbon-coated sodium manganese vanadium phosphate half-cell prepared in Example 1 of the present application;

[0039] Figure 4 This is a cycle performance diagram of the carbon-coated sodium manganese vanadium phosphate half-cell prepared in Example 1 of the present application at a current density of 10C;

[0040] Figure 5 This is a scanning electron microscope image of the carbon-coated sodium manganese vanadium phosphate prepared in Example 2 of the present application;

[0041] Figure 6 This is the XRD pattern of the carbon-coated sodium manganese vanadium phosphate prepared in Example 2 of the present application;

[0042] Figure 7 This is a rate performance diagram of the carbon-coated sodium manganese vanadium phosphate half-cell prepared in Example 2 of the present application;

[0043] Figure 8 This is a cycling performance diagram of the carbon-coated sodium manganese vanadium phosphate half-cell prepared in Example 2 of the present application at a current density of 10C. DETAILED DESCRIPTION

[0044] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0045] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.

[0046] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.

[0047] The following examples and experimental examples use a scanning electron microscope (SEM, JSM-7900F) to analyze the sample morphology; an X-ray diffractometer (XRD, SmartLab) is used to analyze the sample composition; and a LAND CT3001A battery system (Wuhan Landian Electronics Co., Ltd.) is used to test the electrochemical performance. The room temperature in the following examples refers to "25°C".

[0048] Example 1

[0049] 3.6763g sodium citrate, 2.3396g ammonium metavanadate, 1.2255g manganese acetate, and 4.3136g ammonium dihydrogen phosphate, with the atomic substance ratio of sodium, vanadium, manganese, and phosphorus being 3:1.6:0.4:3, were used as raw materials. First, ammonium metavanadate and manganese acetate were added to 40mL deionized water, and heated and stirred in an oil bath at 80℃ for 2h. Then, ammonium dihydrogen phosphate and sodium citrate were added, and stirred in an oil bath at 80℃ for 2h at a stirring speed of 350rpm. Then, the temperature was raised to 120℃ in an oil bath, and the stirring speed was 350rpm, and the solution was stirred until it became a gel. Then, it was moved into an oven and dried at 120℃ overnight. The dried precursor was ball milled (300rpm, 3h). Then, an argon atmosphere was used for heat treatment, and the sample was treated by segmented heating. First, it was heated to 350℃ and kept warm for 4h, and then heated to 800℃ and kept warm for 8h. Finally, a carbon-coated sodium manganese vanadium phosphate product is obtained.

[0050] Example 2

[0051] 2.1056g sodium citrate, 2.3396g ammonium metavanadate, 0.4902g manganese acetate, and 3.4509g ammonium dihydrogen phosphate with an atomic substance ratio of 3.2:1.8:0.2:3 for sodium, vanadium, manganese, and phosphorus were used as raw materials. First, ammonium metavanadate and manganese acetate were added to 40mL deionized water and heated and stirred at 80℃ for 2h. Then ammonium dihydrogen phosphate and sodium citrate were added and stirred at 80℃ for 2h at a stirring speed of 350rpm. Then the temperature was raised to 120℃, the stirring speed was 350rpm, and the solution was stirred until it became a gel. Then it was moved into an oven and dried at 120℃ overnight. The dried precursor was ball milled (300rpm, 3h). Then, an argon atmosphere was used for heat treatment, and the sample was treated by segmented heating. First, it was heated to 350℃ and kept warm for 4h, and then heated to 800℃ and kept warm for 8h. Finally, a carbon-coated sodium vanadium manganese phosphate product was obtained.

[0052] Example 3

[0053] A method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material is as described in Example 1, except that the manganese source is manganese carbonate.

[0054] Example 4

[0055] A method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material is as described in Example 1, except that the manganese source is manganese sulfate.

[0056] Example 5

[0057] A method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material is as described in Example 1, except that the manganese source is manganese chloride.

[0058] Example 6

[0059] A method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material is as described in Example 1, except that the manganese source is manganese oxide.

[0060] Experimental Example 1

[0061] Taking Example 1 as an example, the carbon-coated sodium manganese vanadium phosphate product prepared therefrom was subjected to SEM analysis, XRD analysis and electrochemical performance test:

[0062] The results of SEM and XRD analysis are as follows Figure 1 and Figure 2 As shown. Figure 1 The scanning electron microscope (SEM) image shows that the prepared carbon-coated sodium manganese vanadium phosphate has a porous structure. Figure 2 It can be seen from the X-ray diffraction pattern (XRD) that the prepared carbon-coated sodium manganese vanadium phosphate has good crystallinity.

[0063] The carbon-coated sodium manganese vanadium phosphate prepared in Example 1 was used as the positive electrode of the sodium ion battery and formed a half-cell with the sodium metal negative electrode, and the electrochemical performance of the prepared carbon-coated sodium manganese vanadium phosphate electrode material was tested. The results are as follows Figure 3 and Figure 4 As shown. Figure 3 The rate test shows that the electrode material can provide reversible capacities of 114.4, 111.6, 108.5, 105.1, 99.6, 95.3, 91.5 and 88.5 mAh g at 1, 2, 5, 10, 20, 30, 40 and 50 C. -1 .pass Figure 4 The cycling test shows that at a current density of 10C, the prepared carbon-coated sodium manganese vanadium phosphate electrode still has a capacity of 105.3 mAh g after 2000 cycles. -1 , the capacity retention rate is 95.7%, and it has excellent cycle stability.

[0064] Experimental Example 2

[0065] Taking Example 2 as an example, the carbon-coated sodium manganese vanadium phosphate product prepared therefrom was subjected to SEM analysis, XRD analysis and electrochemical performance test:

[0066] The results of SEM and XRD analysis are as follows Figure 5 and Figure 6 As shown. Figure 5 The scanning electron microscope (SEM) image shows that the prepared carbon-coated sodium manganese vanadium phosphate has a porous structure. Figure 6 It can be seen from the X-ray diffraction pattern (XRD) that the prepared carbon-coated sodium manganese vanadium phosphate has good crystallinity.

[0067] The carbon-coated sodium manganese vanadium phosphate prepared in Example 2 was used as the positive electrode of the sodium ion battery and formed a half-cell with the sodium metal negative electrode. The electrochemical performance of the prepared carbon-coated sodium manganese vanadium phosphate electrode material was tested. The results are as follows: Figure 7 and Figure 8 As shown. Figure 7 The rate test shows that the electrode material can provide reversible capacities of 126, 121, 119, 118, 116, 113, 110 and 107 mAh g at 1, 2, 5, 10, 20, 30, 40 and 50 C. -1 .pass Figure 8 The cycling test shows that at a current density of 10C, the prepared carbon-coated sodium manganese vanadium phosphate electrode still has a capacity of 111 mAh g after 800 cycles. -1 , the capacity retention rate is 93.5%, and it has excellent cycle stability.

[0068] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material, characterized in that: The steps include: (1) heating a mixture containing a sodium source, a vanadium source, a manganese source, a phosphorus source, a carbon source, and water for 1 h, stirring until a gel is formed, and drying to obtain a precursor; (2) ball milling the precursor, and then heating it in an inert gas atmosphere II to obtain the carbon-coated sodium manganese vanadium phosphate positive electrode material.

2. The method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material according to claim 1, characterized in that: The atomic substance ratio of sodium, vanadium, manganese and phosphorus in the sodium source, vanadium source, manganese source and phosphorus source in step (1) is 3-4:1-2:0-1:

3.

3. The method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material according to claim 1, characterized in that: The heating I in step (1) includes heating I-1 and heating I-2; The temperature of the heating I-1 is 60 to 100° C.; The heating time of I-1 is 1 to 3 hours; The temperature of the heating I-2 is 100-200°C.

4. The method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material according to claim 1, characterized in that: The sodium source in step (1) includes sodium citrate and / or sodium carbonate; Preferably, the vanadium source in step (1) comprises one or more of ammonium metavanadate, sodium vanadate, vanadium pentoxide, hydrated vanadium oxalate and vanadium chloride; Preferably, the manganese source in step (1) comprises one or more of manganese acetate, manganese carbonate, manganese sulfate, manganese chloride and manganese carbonate; Preferably, the phosphorus source in step (1) comprises one or more of diammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphoric acid; Preferably, the carbon source in step (1) comprises one or more of sodium citrate, citric acid, glucose and hexadecyltrimethylammonium bromide.

5. The method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material according to claim 1, characterized in that: The stirring speed in step (1) is 300 to 1000 rpm; Preferably, the drying temperature in step (1) is 100-200°C.

6. The method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material according to claim 1, characterized in that: The heating II in step (2) is staged heating; The staged heating is firstly heating to 300-400° C., keeping the temperature for 3-5 hours, and then heating to 700-900° C., keeping the temperature for 6-10 hours.

7. The method for preparing a carbon-coated sodium manganese vanadium phosphate positive electrode material according to claim 1, characterized in that: The rotation speed of the ball mill in step (2) is 300-400 rpm; Preferably, the inert gas in step (2) comprises argon or nitrogen.

8. The carbon-coated sodium manganese vanadium phosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the carbon-coated sodium manganese vanadium phosphate positive electrode material according to claim 8 in the preparation of sodium ion batteries.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the carbon-coated sodium vanadium manganese phosphate positive electrode material according to claim 8.